Analysis of The Prevalence of Stunting Rates in Provinsi Jawa Barat, Bandung - Devi Savitri Effendy; Nur Azizah Rianty Gamoro; Nayla Azizah; Rencong Pandelaki (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Stunting is a chronic growth disorder in children under five, defined as a height-for-age z-score below minus two standard deviations from the WHO Child Growth Standards median. Southeast Asia has one of the highest stunting burdens globally, and Indonesia remains among the countries with a high prevalence. Within West Java Province, Bandung Regency was reported as one of the districts with the fifth-highest stunting prevalence in 2022. Objectives: This study aims to describe the trend of stunting prevalence in West Java Province, with a particular focus on Bandung City, during the period 2018–2022. Methods: This study applied a quantitative descriptive approach to characterize stunting prevalence trends in West Java Province, with a specific focus on Bandung City. Secondary data were obtained from the Indonesian Nutrition Status Survey (SSGI) for West Java Province published by the Ministry of Health of the Republic of Indonesia. The analysis used stunting prevalence estimates from 2018 to 2022 and summarized temporal patterns across the observation period. Results: The trend analysis indicated that stunting prevalence in Bandung City declined in 2019 to 27.1% but increased sharply in 2020 to 35%. These fluctuations suggest that stunting is not solely a nutritional problem but a multidimensional condition shaped by interrelated determinants. Key contributing factors include inadequate dietary intake, maternal and child health status, household socioeconomic constraints, and an unsupportive living environment. Limited access to health services, safe water, and adequate sanitation further exacerbates the risk of impaired linear growth. Conclusion: Stunting represents a complex public health issue reflecting nutritional, social, economic, and environmental vulnerabilities. In Bandung City, prevalence decreased in 2019 but rose again in 2020 and remained above the WHO threshold in 2022, underscoring the need for integrated and sustained interventions. Keywords: stunting; prevalence; West Java; Bandung City; SSGI.